Copper-coated hollow glass microspheres filled rubber composites: Lightweight, interface bonding and mechanical properties - Leyuan Ma; Yiming Wang; Xin Zhang; Shibao Wen; Zhen Yu; Zhenxiu Zhang (eXPRESS Polymer Letters, 2023)
In this work, cis-1,4-polybutadiene rubber/polystyrene-butadiene rubber (BR/SBR) blend was filled with inorganic lightweight filler hollow glass microspheres (HGMs) to develop a rubber-based lightweight composite. Cu-plating was carried out on the surface of HGMs by polydopamine (PDA) and Ag nanoparticles to improve the compatibility among HGMs and rubber matrix. Filter paper experiment, X-ray energy dispersive spectroscopy (EDS) and X-ray photoelectron spectrometer (XPS) were used to analyze the bonding mechanism between Cu-plated HGMs and rubber. The results confirmed that the redox reaction between the reactive sulfur in the rubber matrix and Cu on the surface of Cu-plated HGM can be successfully carried out at 170°C. And the compatibility between HGM and rubber matrix was obviously improved after Cu plating. The physical-mechanical properties and abrasion resistance of the composites were improved significantly. This research was of great significance to marine flexible floating body materials.